2015
DOI: 10.1016/j.ultsonch.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the sonophoresis effect on the permeation of diclofenac sodium using 3D skin equivalent

Abstract: Ultrasound temporally increases skin permeability by altering stratum corneum SC function (sonophoresis). The objective of this study was to evaluate the effect of variable ultrasound conditions on the permeation of diclofenac sodium DS with range of physicochemical properties through EpiDerm™. Permeation studies were carried out in vitro using Franz diffusion cell. HPLC method was used for the determination of the concentration of diclofenac sodium in receiving compartment. Parameters like ultrasound frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…Sodium fluorescein is a highly polar, water‐soluble compound, and its permeation across the skin is known to be poor. The transport of this dye has been used as an indicator to assess the extent of barrier intactness of the stratum corneum . In the present experiment, the content of sodium fluorescein retained in the scar and normal skin epidermis did not differ significantly (56.31 ± 3.46 ng/mg in scar vs. 65.92 ± 3.74 ng/mg in normal skin epidermis).…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…Sodium fluorescein is a highly polar, water‐soluble compound, and its permeation across the skin is known to be poor. The transport of this dye has been used as an indicator to assess the extent of barrier intactness of the stratum corneum . In the present experiment, the content of sodium fluorescein retained in the scar and normal skin epidermis did not differ significantly (56.31 ± 3.46 ng/mg in scar vs. 65.92 ± 3.74 ng/mg in normal skin epidermis).…”
Section: Resultscontrasting
confidence: 41%
“…The transport of this dye has been used as an indicator to assess the extent of barrier intactness of the stratum corneum. [27][28][29][30] In the present experiment, the content of sodium fluorescein retained in the scar and normal skin epidermis did not differ significantly (56.31 ± 3.46 ng/mg in scar vs. 65.92 ± 3.74 ng/mg in normal skin epidermis). However, the passive permeation flux of sodium fluorescein across the scar skin epidermis was 1.11 ± 0.35 ng/(cm 2 h), which is almost one-third of that observed across the normal skin epidermis [2.96 ± 0.63 ng/(cm 2 h)].…”
Section: Passive Transport Of Sodium Fluoresceinmentioning
confidence: 66%
“…US at 20 kHz is applied not only in industry but also to improve the in vitro and in vivo bio-effects in medicine (9)(10)(11). In vitro studies have demonstrated that 20 kHz US enhances the permeation of diclofenac sodium across EpiDerm™ 5-fold (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that 20 kHz US enhances the permeation of diclofenac sodium across EpiDerm™ 5-fold (9)(10)(11). It is a unique and exciting theranostic modality that can be used to track drug carriers, trigger drug release and improve drug deposition to tumor cells with high spatial precision (9).…”
Section: Introductionmentioning
confidence: 99%
“…Untill 2010, Baris E. Polat, Blankschtein D., and Langer R. [4] have reviewed plenty of different drugs whose permeation through the stratum corneum has been enhanced. Recently, Mai Aldwaikat and Mohammed Alarjah [6] also found that ultrasound technology enhanced the permeation of diclofenac sodium through EpiDerm™ (a three-dimension viable skin) fivefold. As a whole, LFS is a valuable transdermal enhancing method, especially for hydrophobic permeants.…”
Section: Introductionmentioning
confidence: 99%